Contactless Multispectral Palm-Vein Recognition With Lightweight Convolutional Neural Network - Yung-Yao Chen (IEEE, 2021)
The development of information technology has made it possible to replace traditional keys and passwords with biometric recognition. Among the various human recognition technologies, contactless palm-vein authentication is becoming increasingly popular because it is hygienic and safe. In the field of deep learning (DL), system security and multispectral compatibility are crucial issues that require outright solutions. One of the most widely investigated DL algorithms is the convolutional neural network (CNN), which has been proven to have strong feature extraction capability. However, the training of CNN requires large samples and thus entails a heavy computational load, resulting in high hardware and software costs. Therefore, this paper proposes an adaptive Gabor filter with enhanced imaging features and triplet loss function that captures sufficient palm-vein data. A multispectral palm database from the CASIA public database was employed in this study to analyze the proposed system. The experimental results show that the proposed method has a low recognition error rate of 0.0556% and uses only a few network parameters in a multispectral environment.